Adjoint estimation and interpretation of spatially varying bottom friction coefficients of the M2 tide for a tidal model in the Bohai, Yellow and East China Seas with multi-mission satellite observations. (May 2021) - Qian, Suhui; Wang, Daosheng; Zhang, Jicai; Li, Chunyan
Abstract: In order to estimate the spatially varying bottom friction coefficients (BFCs) in the Bohai, Yellow and East China Seas (BYECS), multi-mission satellite observations from TOPEX/Poseidon, Jason-1 and Jason-2 are assimilated into a two-dimensional tidal model with an adjoint method. This work aims to: (1) study the characteristics of spatially varying BFCs in BYECS; and (2) find out the possible sources and mechanisms of spatially varying BFCs. In the numerical experiment, the M 2 tide is simulated and the spatially varying BFCs in BYECS are estimated by assimilating observations from tidal gauge stations and multi-mission altimeters. The simulated M 2 tide matches well with the tide gauge data, indicating the reasonability of present methodology of spatially varying BFCs. The characteristics and possible mechanisms of the spatially varying BFCs in BYECS are concluded and discussed, and the main conclusions include: (1) the values of BFCs in shallow water are usually larger than those in deep water, which can reach the order of 10 −2 in shallow areas; (2) the values of BFCs generally decrease with the strengthened depth-averaged tidal current velocity in BYECS; (3) the high-value BFC areas near the coasts always appear in the downstream sides of headlands or peninsulas, which are possibly caused by the propagation of tidal waves; (4) the high-value BFC area along Jiangsu coast is affected by the bottom morphology of radially distributed tidal sand ridges, which might enhance the form drag; (5) the high-value BFC areas in the middle of the South Yellow Sea and Fujian coast correspond to the muddy areas, where the mixture of different sediment types changes the bottom roughness. Highlights: The bottom friction coefficients in some shallow waters can reach the order of 10 -2 . High-value bottom friction coefficients near coasts always appear in the lee of headlands. Different sediment types and environments can affect the bottom friction coefficient.